Diaquabis(4-carboxy-2-ethyl-1H-imidazole-5-carboxylato-κ2N3,O4)zinc N,N-dimethylformamide disolvate - Cheng-Jun Hao (Acta Crystallographica Section E, 2011)
In the title compound, [Zn(C7H7N2O4)2(H2O)2]·2C3H7NO, the ZnII ion, which lies on a center of inversion, is coordinated by two O atoms and two N atoms from two 4-carboxy-2-ethyl-1H-imidazole-5-carboxylato anions and two water O atoms in an octahedral environment, Each 4-carboxy-2-ethyl-1H-imidazole-5-carboxylato ligand adopts a bidentate chelating mode to the ZnII ion, forming two five-membered metalla rings. In the crystal, a two-dimensional framework parallel to (010) is formed by N—H...O and O—H...O hydrogen bonds.